Correlation of oxygen vacancies to various properties of amorphous zinc tin oxide films - Sung, Nark-Eon; Lee, Han-Koo; Chae, Keun Hwa; Singh, Jitendra Pal; Lee, Ik-Jae (AMER INST PHYSICS, 2017)
Amorphous ZnO-SnO2 (a-ZTO) films were deposited on quartz substrates at working pressures of 5 <= P-W <= 12 mTorr using radio frequency sputtering. PW affected the occurrence of oxygen deficiencies in the films. X-ray photoemission spectroscopy, near edge X-ray absorption fine structure (NEXAFS), and ultraviolet photoelectron spectroscopy-based spectroscopy analyses showed that oxygen vacancies (OVs) influence the evolution of the optical and electrical properties of a-ZTO films. NEXAFS reflects the onset of OVs. Low P-W contributes to the evolution of a chemical structure with numerous OVs. This result can be applied to improve the electro-optical properties of a-ZTO films. As P-W decreased, the carrier concentration increased, carrier mobility increased, and film resistivity decreased. Average optical transmittance in the visible region was >90%, and increased as P-W decreased. Published by AIP Publishing.
Keywords: PULSED-LASER DEPOSITION; SENSITIZED SOLAR-CELLS; ZNO THIN-FILMS; OPTICAL-PROPERTIES; DOPED ZNO; STANNATE; SUBSTRATE; ZN2SNO4; PHOTOLUMINESCENCE; TEMPERATURE